Manajemen Risiko pada Perusahaan Asuransi Syariah di Indonesia - Aliefah, Aniesatun Nurul; Marsatiya, Hanifah; Kusumaningrum, Putri; Amrulloh, Akrom (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2024)
This study aims to find out how underwriting risk management in Sharia insurance companies in Indonesia. This research uses a descriptive qualitative approach, which is based on secondary data obtained from books, journals and other supporting documents relevant to the research conducted. The results of this study show that risk management in Sharia insurance is one of the important aspects that must exist to achieve the goals of a company. Risk management is a collection of actions used to find, measure, supervise and manage risks that will arise in the future in non-bank financial institutions. The types or categories of risk include Increasing risk, Decreasing Risk, and Constant Extra Risk. The underwriting process that sharia insurance companies go through includes submitting a request letter, risk analysis, then issuing a policy. Keywords : Risk Management, Sharia Insurance, Underwriting